Effect of elevation on composition and diversity of fungi in the rhizosphere of a population of Deyeuxia angustifolia on Changbai Mountain, northeastern China - Sui, Xin; Li, Mengsha; Frey, Beat; Dai, Guanhua; Yang, Libin; Li, Mai-He (Frontiers in Microbiology, 2023)
Soil fungi are a key component of terrestrial ecosystems and play a major role in soil biogeochemical cycling. Although the diversity and composition of fungal communities are regulated by many abiotic and biotic factors, the effect of elevation on soil fungal community diversity and composition remains largely unknown. In this study, the soil fungal composition and diversity in Deyeuxia angustifolia populations along an elevational gradient (1690 m to 2020 m a.s.l.) were assessed, using Illumina MiSeq sequencing, on the north-facing slope of the Changbai Mountain, northeastern China. Our results showed that soil physicochemical parameters changed significantly along with the elevational gradients. The Ascomycota and Basidiomycota were the most dominant phyla along with the gradient. Alpha diversity of soil fungi decreased significantly with elevation. Soil nitrate nitrogen (NO3--N) was positively correlated with fungal richness and phylogenetic diversity (PD), indicating that soil nitrate nitrogen (NO3--N) is a key soil property determining fungal community diversity. In addition to soil nitrate content, soil pH and soil moisture were the most important environmental properties determining the soil fungal diversity. Our results suggest that the elevational changes in soil physicochemical properties play a key role in shaping the community composition and diversity of soil fungi. This study will allow us to better understand the biodiversity distribution patterns of soil microorganisms in mountain ecosystems.